COMPOSIÇÃO FLORÍSTICA E CRESCIMENTO DE BRANQUILHO EM DIFERENTES CONDIÇÕES DA FLORESTA OMBRÓFILA MISTA ALUVIAL - Guilhermeti, Paulo Gabriel Caleffi (2015)
The objective of this paper was to evaluate the composition and floristic distribution, and the influence of environmental variables over the soil polyhydric gradient through multivariate techniques, and analyze and correlate the growth of S. commersoniana with climate variables in a fragment of the Mixed Rain Forest Alluvial in Guarapuava - PR. For the study the sample units were used constituted from three transects (A, B and C), these were subdivided into 42 sample subunits, with 10 x 10 meters parcels. The trees that have the Diameter at breast height (DBH) ? 5 cm were measured and identified. The data of vegetation (abundance, divercidade and basal area) were correlated by multivariate techniques with different environmental variables (water level, soil moisture, penetration resistance, moisture (deformed samples) and chemical variables and soil physics). The TWINPAN clustering technique presented sensitivity in group terms in similar characteristic functions while and Canonical Correspondence technique showed that Sebastiania commersoniana, Ligustrum lucidum and Allophylus edulis are more correlated with pH variables. The water level base saturation and basal area, while Matayba elaeagnoide and Ocotea puberula are more correlated with well-drained soil. The other species were highly correlated with resistance to penetration and saturation of aluminum and moderately drained soils. The growth of S. commersoniana was evaluated by means of partial stem analysis from 116 trees, and as a criterion for selection of the samples, we tried to cover trees located in plots with different levels of water saturation and sociological position. The method used to collect the samples was non-destructive, through the auger Pressler (5 mm of diameter) the increment values for S. commersoniana ranged from 1.20 mm / year (undergrowth and low water level) to 1.99 mm / year (Canopy and high water level). These data were correlated with precipitation data, average temperature, minimum and maximum. Through the analysis it was found that S. commersoniana, showed lower growth when they were in a dominated sociological position and high water level. It was observed yet, that the growth of S. commersoniana was correlated negatively with the sum of precipitation for the trees located in high water level. The results show that the excess water is a limiting factor for the distribution of most species of Mixed Rain Forest Alluvial, and even for species adapted to these environments, such as S. commersoniana, high water saturation brings adverse effects on growth.